Great British athletes` perceptions of competing at the London 2012 Olympic Games - Kent, R. (The Sport Journal, 2016)
To review Great British (GB) athletes` perceptions of home court advantage and competing ahead of the 2012 London Olympic Games a qualitative study using semi-structured interviews was conducted. The seven topics discussed in the interview were based on previous research. Five female GB Olympic sprinters were interviewed at their training facility in West London as they trained for the 2012 Olympic Games. Athlete responses were coded into categories then analysed using phenomenological analysis.